The comparative study of chondrogenic differentiation of mesenchymal stromal cells allocated from different sources - Yu. B. Basok; A. M. Grigoriev; L. A. Kirsanova; I. V. Vakhrushev; A. V. Tsvetkova; A. A. Gryadunova; K. N. Yarygin; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2019)
Introduction. As an alternative to autochondral transplantation, variants of chondrocyte replacement with mesenchymal stromal cells (MSCs) were considered, since these cells are present in all organs and tissues of human body and possess multilinear potential for differentiation. A number of studies demonstrate that the ability for chondrogenic differentiation of MSCs from different tissues varies, however, those studies are few and controversial. In accordance with the ethical principles and the technical ease of obtaining, adipose tissue, Wharton’s jelly (stroma) and dental pulp are the most attractive sources of MSCs for tissue engineering.Aim: to compare the chondrogenic potential of MSCs allocated from adipose tissue, Wharton’s jelly of the umbilical cord, and human deciduous teeth pulp cultured in the composition of microspheres (pellets).Materials and methods. The phenotype of primary cultures of MSCs was studied via flow microscopy. Chondrogenic differentiation was performed with 3D-culture in microspheres in the presence of TGFβ1 for two weeks under standard conditions. Human chondroblasts were used as a positive control. Cell viability was determined by fluorescent staining. Morphological study was performed using histological and immunohistochemical staining methods.Results. Cultures of MSCs from all sources had similar phenotypes CD29+, CD34–, CD44+, CD49b+, CD45–, CD73+, CD90+, HLADR. In the mass of living cells in microspheres only singular dead cells were visualized. A significant production of extracellular matrix (ECM) was observed in the chondroblast and adipose tissue microspheres, whereas in the microspheres of dental pulp and umbilical cord stroma derived MSCs, no significant ECM was detected. Among the MSCs, the highest production of collagen and glycosaminoglycans (GAG) in the ECM was observed in the microspheres of adipose tissue-derived MSCs, and the lowest production – in the microspheres of dental pulp-derived MSCs. Conclusion. A histological analysis of all microspheres after 14 days of culturing in the chondrogenic medium revealed the signs of differentiation in the chondrogenic direction, a progressive increase of the ECM produced by cells, and the presence of total collagen and GAG in it. Of all the MSCs studied, the greatest chondrogenic potential in vitro (the intensity of development of ECM components) is possessed by the adipose tissue-derived MSCs.